LABOR COST ANALYSIS ON THE ACCELERATION OF ARCHITECTURAL WORK IMPLEMENTATION (CASE STUDY: FACULTY OF ECONOMICS AND BUSINESS BUILDING, UNIVERSITAS NEGERI SEMARANG) - Rendi Tonga Syaputra; Muhammad Faizal Ardhiansyah Arifin (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
Time and cost control are critical aspects in construction project implementation, particularly in architectural works that heavily depend on labor productivity. Delays in work completion may significantly increase labor costs. This study aims to compare normal scheduling and accelerated scheduling using the Precedence Diagram Method (PDM) and to analyze their impact on project duration and labor costs. The case study was conducted on the construction project of the Faculty of Economics and Business Building at Universitas Negeri Semarang, focusing on architectural works of the Basement and First floors. A quantitative method was employed using secondary data, including the Bill of Quantity, Budget Plan, weekly reports, and labor productivity data. The results indicate that normal scheduling produced a total duration of 478 days, while accelerated scheduling using PDM reduced the duration to 352 days and generated labor cost savings of Rp24,967,750. These findings demonstrate that PDM effectively improves time and labor cost efficiency in architectural building projects.